Efficiency, state of unconstitutional things about displaced population rights in Colombia - Avella Gallego, Carolina; Gabriel Martínez, Jesús; Nitola Cardozo, Diego Felipe; Niño Hernández, Wilmar; Avella Gallego, Carolina; Gabriel Martínez, Jesús; Nitola Cardozo, Diego Felipe; Niño Hernández, Wilmar; Avella Gallego, Carolina; Gabriel Martínez, Jesús; Nitola Cardozo, Diego Felipe; Niño Hernández, Wilmar (Corporación Universitaria Americana, 2020)
This article elaborates an analysis and description of the state of unconstitutional things about forced displacement victims in Colombia, declared through the decree T-025 and the resolution 373 of 2016, by a general panorama, where the study of this structural failure expose the circumstances that displaced people are in when the T-02/04 was announced, the evolution of its events and governmental acts facing the Constitutional Court response, in this way new categories that describe the socio-juridical phenomenon and its development are proposed, presenting "The New State of Unconstitutional Things".